Method for preparing 3, 4-dihydropyran

By using titanium-aluminum composite oxide catalyst, the problem of easy deactivation of γ-alumina catalyst was solved, and the effect of efficient conversion of tetrahydrofurfuryl alcohol to 3,4-dihydropyran was achieved, and the stability and reaction efficiency of the catalyst were improved. .

CN119490476APending Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311018871.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, γ-alumina catalysts are prone to deactivate during the preparation of 3,4-dihydropyran by dehydration of tetrahydrofurfuryl alcohol, and have a short life, resulting in a decrease in yield and an increase in energy consumption.

Method used

The titanium-aluminum composite oxide catalyst is prepared by co-precipitation method to regulate the acidity of the catalyst surface and increase the incorporation of titanium oxide to reduce the L acidity of the alumina surface and improve the stability of the catalyst.

Benefits of technology

The service life of the catalyst was significantly improved, the conversion rate of tetrahydrofurfuryl alcohol reached 99%, the selectivity of 3,4-dihydropyran reached 98%, and the energy consumption and material consumption were reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004392954970000041
    Figure BDA0004392954970000041
  • Figure BDA0004392954970000051
    Figure BDA0004392954970000051
  • Figure BDA0004392954970000052
    Figure BDA0004392954970000052
Patent Text Reader

Abstract

The invention relates to a method for preparing 3, 4-dihydropyran. According to the method, tetrahydrofurfuryl alcohol is adopted as a reactant, and under the catalytic action of a titanium-aluminum composite oxide catalyst, 3, 4-dihydropyran is prepared through a reaction. The reaction conditions are as follows: the reaction is carried out in a fixed bed reactor at normal pressure, the reaction temperature is 250-350 DEG C, and the feeding mass space velocity of tetrahydrofurfuryl alcohol is 0.1-2.0 h <-1 >. The method is characterized in that the surface acidity of the titanium-aluminum composite oxide catalyst can be regulated and controlled through a preparation process, the L acidity of the surface of aluminum oxide is effectively reduced by doping titanium oxide, the high catalytic activity of aluminum oxide is reserved, meanwhile, good carbon deposition resistance and poisoning resistance are achieved, and the service life of the catalyst is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing 3,4-dihydropyran, and in particular to a method for preparing 3,4-dihydropyran by dehydrating tetrahydrofurfuryl alcohol using a titanium-aluminum composite oxide catalyst. Background Art

[0002] As the only renewable carbon resource in nature, biomass can be used to produce liquid fuels, platform chemicals, high value-added chemicals, etc. through the biorefining process. Furfural is one of the largest biomass-based platform chemicals today, with a global available production capacity of more than 600kt / a, and has the potential to become a major substitute for fossil resources. Furfural is hydrogenated in the gas phase to produce tetrahydrofurfuryl alcohol (THFA), which can be dehydrated in the gas phase to produce 3,4-dihydropyran (DHP). DHP is a six-membered oxygen-containing heterocyclic compound that can be used as a pharmaceutical intermediate and alcohol group protection reagent; it is widely used as a hydroxyl group protection reagent; DHP has active chemical properties and can be used to produce tetrahydropyran, pentanediol, glutaric acid, valerolactone, pentadiene and resin products through polymerization, hydrogenation, oxidation and other reactions. The preparation of DHP by dehydration of tetrahydrofurfuryl alcohol has important industrial significance in the fields of organic chemistry and polymer materials.

[0003] The existing DHP synthesis process mainly uses activated γ-alumina as a catalyst to make tetrahydrofurfuryl alcohol undergo ring expansion and dehydration under high temperature conditions. Since the surface of activated alumina has a strong L-acid center, it is both the active center of the catalytic reaction and the carbon deposition center of the reaction. In the early stage of the reaction, the strong L-acid center on the surface of highly active activated alumina is prone to carbon deposition, resulting in the active center of the γ-alumina catalyst being covered, so that the yield of DHP is only high in the initial stage and the catalyst is rapidly deactivated. In view of the problem of rapid deactivation of the above-mentioned γ-alumina catalyst, it is imperative to develop a new catalytic system for the dehydration of tetrahydrofurfuryl alcohol to produce DHP, improve the conversion efficiency and stability of the catalyst, and further reduce the energy consumption and material consumption of the dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran. Summary of the invention

[0004] The significance of the invention is to overcome the shortcomings of easy deactivation and short life of the catalyst in the process of preparing 3,4-dihydropyran by dehydration of tetrahydrofurfuryl alcohol, develop a new catalytic system and catalytic reaction process for preparing 3,4-dihydropyran by converting tetrahydrofurfuryl alcohol, and improve the conversion efficiency and the stability of the catalyst.

[0005] The objective of the present invention is achieved through the following technical scheme: a method for preparing 3,4-dihydropyran, characterized in that the raw material is tetrahydrofurfuryl alcohol, the catalyst is a titanium aluminum composite oxide catalyst, the product is 3,4-dihydropyran, and the reaction temperature is 250°C-350°C, preferably 280°C-320°C.

[0006] The preparation method of the titanium-aluminum composite oxide is a co-precipitation method, and the specific preparation method is: mixing metal aluminum salt and metal titanium salt solution, adjusting the pH to 9-10.5 with ammonia water; aging the obtained precipitate in the mother liquor, washing with deionized water, filtering until there is no chloride ion, putting it in an oven to dry, and then calcining it in a muffle furnace to obtain the titanium-aluminum composite oxide.

[0007] The metal aluminum salt includes one or more of aluminum nitrate, aluminum trichloride, aluminum sulfate, sodium metaaluminate, and aluminum isopropoxide.

[0008] The metal titanium salt includes one or more of titanium tetrachloride, titanyl sulfate, titanium isopropoxide and titanium sulfate.

[0009] The mass content of aluminum oxide in the titanium aluminum composite oxide catalyst is 75wt%-99wt%, preferably 85wt%-95wt%.

[0010] The aging time of the titanium aluminum composite oxide catalyst in the mother liquor is 1-24 hours, preferably 2-12 hours; the drying temperature is 80-150 degrees, preferably 100-120 degrees; the calcination temperature is 40°C-1200°C, preferably 500°C-800°C.

[0011] The device is a fixed bed reactor, and the reaction is carried out at normal pressure.

[0012] After the titanium aluminum composite oxide catalyst is filled in the reaction tube, the reaction is placed in a fixed bed reactor for reaction.

[0013] The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.1-3.0h -1 , the catalyst bed thickness is 10mm-50mm.

[0014] The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.5-0.8h -1 , the catalyst bed thickness is 20mm-30mm.

[0015] The beneficial effects of the present invention are:

[0016] (1) The surface acidity of titanium-aluminum composite oxide catalysts can be regulated through the preparation process. The addition of titanium oxide effectively reduces the L acidity of the aluminum oxide surface, retaining the high catalytic activity of aluminum oxide while having good resistance to carbon deposition and poisoning.

[0017] (2) The catalytic system has certain advantages in catalyzing tetrahydrofurfuryl alcohol to prepare 3,4-dihydropyran. The conversion rate of tetrahydrofurfuryl alcohol reaches 99%, the selectivity of 3,4-dihydropyran reaches 98%, and the catalyst life exceeds 2000 hours.

[0018] The method is characterized in that the surface acidity of the titanium-aluminum composite oxide catalyst can be regulated through the preparation process, and the incorporation of titanium oxide effectively reduces the L acidity of the aluminum oxide surface, retaining the high catalytic activity of aluminum oxide while having good resistance to carbon deposition and poisoning, and the service life of the catalyst is significantly improved. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

[0020] All raw materials of the present invention are not particularly limited in purity, and the reagents used in the following examples are all commercially available. Qualitative analysis of the reaction product: Agilent gas chromatography-mass spectrometry is used to qualitatively analyze the reaction product 1,5-pentanediol, which is confirmed by mass spectrometry library retrieval combined with standard substance retention time comparison. Quantitative analysis of the reaction product: Agilent gas chromatography-mass spectrometry is used to qualitatively analyze the reaction products 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran, which are confirmed by mass spectrometry library retrieval combined with standard substance retention time comparison. Quantitative analysis of the reaction product: Agilent gas chromatograph (chromatographic column is FFAP capillary column, FID hydrogen ion flame detector) is used to quantitatively analyze the product by internal standard method, and the internal standard is N, N-dimethylformamide. Drawing of internal standard working curve: accurately weigh 4.0g of N,N-dimethylformamide, the standard substance of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran, to prepare the standard solution mother solution, then transfer 0.2g, 0.4g, 0.6g, 0.8g, and 1.0g from the mother solution respectively, dissolve 0.25N,N-dimethylformamide, add 1.5mL acetonitrile to make up the volume, and then perform gas phase analysis to record the analytes (tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran) respectively. The peak area ratio of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, 2-hydroxytetrahydropyran) and standard N,N-dimethylformamide (Ai / As, where Ai represents the chromatographic peak area of ​​the analyte and As represents the chromatographic peak area of ​​the standard) is taken as the horizontal coordinate, and the mass ratio mi / ms of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, 2-hydroxytetrahydropyran and N,N-dimethylformamide in each solution is calculated as the vertical coordinate, and the standard working curve of the raw material and the product is drawn to calculate the yield of the product. In the following examples, the conversion rate of tetrahydrofurfuryl alcohol and the selectivity of 3,4-dihydropyran, tetrahydropyran and 2-hydroxytetrahydropyran are defined by the following formula:

[0021]

[0022]

[0023]

[0024]

[0025] 3,4-dihydropyran yield (%) = 3,4-dihydropyran selectivity * tetrahydrofurfuryl alcohol conversion rate * 100

[0026] Tetrahydropyran yield (%) = Tetrahydropyran selectivity * Tetrahydrofurfuryl alcohol conversion rate * 100

[0027] 2-Hydroxytetrahydropyran selectivity (%) = 2-Hydroxytetrahydropyran selectivity * tetrahydrofurfuryl alcohol conversion rate * 100

[0028] Example 1

[0029] Preparation of 15wt% TiO2 / titanium-aluminum composite oxide:

[0030] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water. Drop 3.60g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH of 5.5 in this case), hydrolyze in an ice-water bath for 1 hour, slowly mix the aluminum nitrate solution with the titanium tetrachloride solution, then drop concentrated ammonia (ammonia content 25% to 28%, the same below) while stirring until pH reaches 9-10.5 (pH of 9.5 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until free of chloride ions, put into an oven and dry at 105 degrees Celsius for 12 hours, then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain a 15wt% TiO2 / titanium-aluminum composite oxide, which is designated as catalyst 1#.

[0031] Example 2

[0032] Preparation of 1.0wt% TiO2 / titanium-aluminum composite oxide:

[0033] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water. Drop 0.21g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH of 5.8 in this case), and hydrolyze in an ice-water bath for 1 hour. Slowly mix the aluminum nitrate solution and the titanium tetrachloride solution, and then drop concentrated ammonia water while stirring until the pH reaches 9-10.5 (pH of 10.5 in this case). Age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, and then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain 1.0wt% TiO2 / titanium-aluminum composite oxide, which is recorded as catalyst 2#.

[0034] Example 3

[0035] Preparation of 5.0wt% TiO2 / titanium-aluminum composite oxide:

[0036] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water; drop 1.07g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH of 5.2 in this case); hydrolyze in an ice-water bath for 1 hour; slowly mix the aluminum nitrate solution and the titanium tetrachloride solution; then drop concentrated ammonia water while stirring until the pH is 9-10.5 (pH of 9.1 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours; then wash with deionized water and filter by suction until there is no chloride ion; dry in an oven at 105 degrees Celsius for 12 hours; then convert and roast in a muffle furnace at 500 degrees Celsius for 2 hours to obtain a 5.0wt% TiO2 / titanium-aluminum composite oxide, which is designated as catalyst 3#.

[0037] Example 4

[0038] Preparation of 10.0wt% TiO2 / titanium-aluminum composite oxide:

[0039] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water. Drop 2.26g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH=6 in this case), and hydrolyze in an ice-water bath for 1 hour. Slowly mix the aluminum nitrate solution and the titanium tetrachloride solution, and then drop concentrated ammonia water while stirring until the pH is 9-10.5 (pH=10.2 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until there is no chloride ion, put it in an oven and dry it at 105 degrees Celsius for 12 hours, and then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain a 10.0wt% TiO2 / titanium aluminum composite oxide, which is recorded as catalyst 4#.

[0040] Example 5

[0041] Preparation of 20.0wt% TiO2 / titanium-aluminum composite oxide:

[0042] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water. Drop 5.10g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH 5.6 in this case), and hydrolyze in an ice-water bath for 1 hour. Slowly mix the aluminum nitrate solution and the titanium tetrachloride solution, and then drop concentrated ammonia water while stirring until the pH is 9-10.5 (pH 9.8 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until there is no chloride ion, put it in an oven and dry it at 105 degrees Celsius for 12 hours, and then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain a 20.0wt% TiO2 / titanium aluminum composite oxide, which is recorded as catalyst 5#.

[0043] Example 6

[0044] Preparation of 25.0wt% TiO2 / titanium aluminum composite oxide:

[0045] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water. Drop 6.79g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH of 5.5 in this case), and hydrolyze in an ice-water bath for 1 hour. Slowly mix the aluminum nitrate solution and the titanium tetrachloride solution, and then drop concentrated ammonia water while stirring until the pH reaches 9-10.5 (pH of 9.6 in this case). Age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, and then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain 25.0wt% TiO2 / titanium-aluminum composite oxide, which is recorded as catalyst 6#.

[0046] Example 7: Changing the aluminum source

[0047] Weigh 40.64g of aluminum chloride hexahydrate and dissolve it in 100mL of deionized water, drop 3.60g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH of 5.5 in this case), hydrolyze in an ice-water bath for 1 hour, slowly mix the aluminum chloride solution with the titanium tetrachloride solution, then drop concentrated ammonia water while stirring until the pH reaches 9-10.5 (pH of 9.5 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter with suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain 15wt% TiO2 / titanium-aluminum composite oxide, which is recorded as catalyst 7#.

[0048] Example 8: Changing the aluminum source

[0049] Weigh 13.84g of sodium aluminate and dissolve it in 100mL of deionized water. Drop 3.60g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH 5.5 in this case), hydrolyze in an ice-water bath for 1 hour, slowly mix the sodium aluminate solution with the titanium tetrachloride solution, then drop into concentrated ammonia while stirring until the pH is 9-10.5 (pH 9.8 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter with suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain 15wt% TiO2 / titanium-aluminum composite oxide, which is designated as catalyst 8#.

[0050] Example 9: Changing the aluminum source

[0051] Take by weighing aluminum isopropylate 34.84g and be dissolved in 100mL deionized water, titanium tetrachloride 3.60g is dropped in the hydrochloric acid solution of 20mL PH=5-6 (being PH=5.5 at this), hydrolyze 1 hour in ice-water bath, aluminum isopropylate solution and titanium tetrachloride solution are slowly mixed, then drop into concentrated ammonia while stirring until PH=9-10.5 (being PH=9.5 at this); Gained precipitate is at room temperature aged 12 hours in reaction solution, then use deionized water washing, suction filtration until no chloride ion, put into baking oven and dry 105 degrees Celsius and dry 12 hours, then convert 500 degrees Celsius of roastings in the muffle furnace 2 hours, obtain 15wt%TiO / titanium aluminum composite oxide, be designated as catalyst 9#.

[0052] Example 10: Changing the aluminum source

[0053] Weigh 28.8g of aluminum sulfate and dissolve it in 100mL of deionized water. Drop 3.60g of titanium tetrachloride into 20mL of hydrochloric acid solution with a pH of 5-6 (pH 5.5 in this case), hydrolyze in an ice-water bath for 1 hour, slowly mix the aluminum sulfate solution and the titanium tetrachloride solution, then drop concentrated ammonia water while stirring until the pH is 9-10.5 (pH 9.4 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter with suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, then convert it into a muffle furnace and roast it at 50 degrees Celsius for 2 hours to obtain 15wt% TiO2 / titanium-aluminum composite oxide, which is designated as catalyst 10#.

[0054] Example 11 Changing the titanium source

[0055] Weigh 63.15 g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100 mL of deionized water. Drop 3.03 g of titanyl sulfate into 20 mL of hydrochloric acid solution with a pH of 5-6 (pH 5.5 in this case), and hydrolyze in an ice-water bath for 1 hour. Slowly mix the aluminum nitrate solution and the titanyl sulfate solution, and then drop concentrated ammonia water while stirring until the pH reaches 9-10.5 (pH 9.9 in this case). Age the resulting precipitate in the reaction solution at room temperature for 12 hours, then wash with deionized water, filter by suction until there is no chloride ion, dry in an oven at 105 degrees Celsius for 12 hours, and then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain a 15wt% TiO2 / titanium-aluminum composite oxide, which is recorded as catalyst 11#.

[0056] Example 12: Changing the titanium source

[0057] Weigh 63.15g of aluminum nitrate (Al(NO3)3.9H2O) and dissolve it in 100mL of deionized water; drip 7.63g of titanium sulfate into 30mL of hydrochloric acid solution with a pH value of 5-6 (pH value of 5.5 in this case); hydrolyze in an ice-water bath for 1 hour; slowly mix the aluminum nitrate solution and the titanium sulfate solution; then drip concentrated ammonia water while stirring until the pH value reaches 9-10.5 (pH value of 9.7 in this case); age the resulting precipitate in the reaction solution at room temperature for 12 hours; then wash with deionized water and filter by suction until there is no chloride ion; dry in an oven at 105 degrees Celsius for 12 hours; then convert and roast in a muffle furnace at 500 degrees Celsius for 2 hours to obtain a 15wt% TiO2 / titanium-aluminum composite oxide, which is designated as catalyst 12#.

[0058] Example 13: Changing the titanium source

[0059] Weigh aluminum nitrate (Al(NO 3 ) 3.9H 2 O) 63.15 g and dissolve it in 100 mL deionized water, drop titanium isopropoxide 5.39 g into 30 mL hydrochloric acid solution of pH=5-6 (pH=5.5 in this case), hydrolyze in an ice-water bath for 1 hour, slowly mix aluminum nitrate solution and titanium isopropoxide solution, then drop into concentrated ammonia while stirring until pH=9-10.5 (pH=9.6 in this case); age the gained precipitate at room temperature in the reaction solution for 12 hours, then wash with deionized water, filter with suction until there is no chloride ion, put into an oven and dry at 105 degrees Celsius for 12 hours, then convert it into a muffle furnace and roast it at 500 degrees Celsius for 2 hours to obtain 15wt% TiO / titanium-aluminum composite oxide, designated as catalyst 13#.

[0060] Examples 14-26

[0061] The catalyst prepared as above was applied to the reaction of catalyzing the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6 mm and a tube length of 400 mm. The thickness of the catalyst bed was 25 mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1 h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 310°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5 h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis.

[0062]

[0063]

[0064] Example 27-30 Reaction Temperature

[0065] 15wt% TiO2 / titanium aluminum composite oxide catalyst-1# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 400mm. The thickness of the catalyst bed was 25mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 250-350°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. The tetrahydrocanol conversion rate and the selectivity of 3,4-dihydropyran are shown in Table 2.

[0066]

[0067] Comparative Example 1

[0068] The activated alumina produced by Shandong Xiguan Alumina Technology Co., Ltd. was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalyst was sieved to 20-40 mesh and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 400mm. The thickness of the catalyst bed was 25mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600℃ for 1h. After the pretreatment, the catalyst bed was cooled to the reaction temperature of 280℃, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 72 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 90% to 70%, and the selectivity of 3,4-dihydropyran decreased from the initial 98% to 95%.

[0069] Comparative Example 2

[0070] Alumina produced by Henan Sanyi Water Treatment Technology Co., Ltd. was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalyst was sieved to 20-40 mesh and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 400mm. The catalyst bed thickness was 25mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600℃ for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 280℃, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 24 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 95% to 65%, and the selectivity of 3,4-dihydropyran decreased from the initial 98% to 80%.

[0071] Comparative Example 3

[0072] Nano-γ-alumina produced by Shanghai Aladdin Biochemical Technology Co., Ltd. was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalyst was pressed into tablets, and the catalyst with a mesh size of 20-40 was sieved and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 400mm. The thickness of the catalyst bed was 25mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600℃ for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 280℃, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 40 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 85% to 50%, and the selectivity of 3,4-dihydropyran increased from the initial 95% to the final 93%.

Claims

1. A method for preparing 3,4-dihydropyran, characterized in that: Tetrahydrofurfuryl alcohol is used as a raw material and titanium aluminum composite oxide is used as a catalyst to produce the product 3,4-dihydropyran, and the reaction temperature is 250°C-350°C, preferably 280°C-320°C; The mass content of titanium oxide in the titanium-aluminum composite oxide catalyst is 25wt%-1.0wt%, preferably 15wt%-5wt%.

2. The method according to claim 1, characterized in that: The preparation method of the titanium-aluminum composite oxide is a coprecipitation method, and the specific process is: adjusting the pH of a mixed solution of metal aluminum salt and metal titanium salt to 9-10.5 with ammonia water; aging, washing with water, drying the precipitate, and then roasting to obtain the titanium-aluminum composite oxide.

3. The method according to claim 2, characterized in that: The metal aluminum salt includes one or more of aluminum nitrate, aluminum trichloride, aluminum sulfate, sodium metaaluminate, and aluminum isopropoxide.

4. The method according to claim 2, characterized in that: The metal titanium salt includes one or more of titanium tetrachloride, titanyl sulfate, titanium isopropoxide and titanium sulfate.

5. The method according to claim 1, characterized in that: The aging time of the titanium-aluminum composite oxide precipitate in the mother liquor is 1-24 hours, preferably 2-12 hours; the drying temperature is 80-150 degrees, preferably 100-120 degrees; the roasting temperature is 40°C-1200°C, preferably 500°C-800°C, and the roasting time is 1-12 hours, preferably 2-4 hours.

6. The method according to claim 1, characterized in that: The device is a fixed bed reactor, and the reaction is carried out at normal pressure.

7. The method according to claim 6, characterized in that: After the titanium aluminum composite oxide catalyst is filled in the reaction tube, the reaction tube is placed in a fixed bed reactor to carry out the reaction.

8. The method according to claim 6 or 7, characterized in that: The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.1-3.0h -1 , the catalyst bed thickness is 10mm-50mm.

9. The method according to claim 8, characterized in that: The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.5-0.8h -1 , the catalyst bed thickness is 20mm-30mm.

Citation Information

Patent Citations

  • Catalyst for preparing furan through furfural gas-phase continuous decarbonylation and preparation method thereof

    CN115845837A

  • Method for producing 3,4-dihydro-2H-pyran

    CN1444577A

  • Process for the preparation of 3,4-dihydro-2H-pyran

    EP0691337A1

  • Process for the manufacture of acrolein from tetrahydrofurfuryl alcohol

    GB569625A

  • Production of 2,3-dihydropyran

    GB858626A